Flow Dynamics and Mixing in Extracorporeal Support: A Study of the Return Cannula - Lemétayer, Julien; Broman, L. Mikael; Prahl Wittberg, Lisa (Frontiers in Bioengineering and Biotechnology, 2021)
Cannulation strategies in medical treatment such as in extracorporeal life support along with the associated cannula position, orientation and design, affects the mixing and the mechanical shear stress appearing in the flow field. This in turn influences platelet activation state and blood cell destruction. In this study, a co-flowing confined jet similar to a return cannula flow configuration found in extracorporeal membrane oxygenation was investigated experimentally. Cannula diameters, flow rate ratios between the jet and the co-flow and cannula position were studied using Particle Image Velocimetry and Planar Laser Induced Fluorescence. The jet was turbulent for all but two cases, in which a transitional regime was observed. The mixing, governed by flow entrainment, shear layer induced vortices and a backflow along the vessel wall, was found to require 9–12 cannula diameters to reach a fully homogeneous mixture. This can be compared to the 22–30 cannula diameters needed to obtain a fully developed flow. Although not significantly affecting mixing characteristics, cannula position altered the development of the flow structures, and hence the shear stress characteristics.